Biosynthesis and Activity of Prenylated FMN Cofactors. Issue 5 (17th May 2018) - Wang, Po-Hsiang; Khusnutdinova, Anna N.; Luo, Fei; Xiao, Johnny; Nemr, Kayla; Flick, Robert; Brown, Greg; Mahadevan, Radhakrishnan; Edwards, Elizabeth A.; Yakunin, Alexander F.
Summary: Prenylated flavin mononucleotide (prFMN) is a recently discovered cofactor required by the UbiD family of reversible decarboxylases involved in ubiquinone biosynthesis, biological decomposition of lignin, and biotransformation of aromatic compounds. This cofactor is synthesized by UbiX-like prenyltransferases catalyzing the transfer of the dimethylallyl moiety of dimethylallyl-monophosphate (DMAP) to FMN. The origin of DMAP for prFMN biosynthesis and the biochemical properties of free prFMN are unknown. We show that in Escherichia coli cells, DMAP can be produced by phosphorylating prenol using ThiM or dephosphorylating DMAPP using Nudix hydrolases. We produced 14 active prenyltransferases whose properties enabled the purification and characterization of protein-free forms of prFMN. In vitro assays revealed that the UbiD-like ferulate decarboxylase (Fdc1) can be activated by free prFMNiminium or C2′-hydroxylated prFMNiminium under both oxidized and reduced conditions. These insights into the biosynthesis and properties of prFMN will facilitate further elucidation of the biochemical diversity of reversible UbiD (de)carboxylases. Graphical Abstract: Highlights: FMN prenylation activity is conserved in the UbiX family E. coli produces DMAP by phosphorylation of prenol and dephosphorylation of DMAPP Identification and biochemical characterization of new forms of prFMN A novel metabolic link between the isoprenoid pathway and ubiquinone biosynthesis Abstract : Wang et al. characterized the biosynthetic origin of the prenyl donor of prenylated FMN in E. coli, a newfound cofactor involved in ubiquinone biosynthesis and lignin biodegradation. They developed methods to produce free prenylated FMN species. These findings suggested a novel metabolic link between the isoprenoid pathway and ubiquinone biosynthesis.